2015
DOI: 10.1038/nrmicro3519
|View full text |Cite
|
Sign up to set email alerts
|

Sexual development in Plasmodium parasites: knowing when it's time to commit

Abstract: Malaria is a devastating infectious disease that is caused by blood-borne apicomplexan parasites of the genus Plasmodium. These pathogens have a complex lifecycle, which includes development in the anopheline mosquito vector and in the liver and red blood cells of mammalian hosts, a process which takes days to weeks, depending on the Plasmodium species. Productive transmission between the mammalian host and the mosquito requires transitioning between asexual and sexual forms of the parasite. Blood- stage paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
195
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 151 publications
(178 reference statements)
6
195
0
5
Order By: Relevance
“…The ortholog of this gene is resistant to genetic disruption in P. berghei (9), and its role in parasite development has not been investigated previously, although its putative function in gametocytogenesis was implicated in a previous study of P. falciparum parasites (24,25). Here, we successfully disrupted the Pyap2-g3 gene and showed that disruption of this gene significantly reduced the numbers of male and female gametocytes (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The ortholog of this gene is resistant to genetic disruption in P. berghei (9), and its role in parasite development has not been investigated previously, although its putative function in gametocytogenesis was implicated in a previous study of P. falciparum parasites (24,25). Here, we successfully disrupted the Pyap2-g3 gene and showed that disruption of this gene significantly reduced the numbers of male and female gametocytes (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Our results also demonstrate that PY17X_1417400 (Pyap2-g3) is a gene that plays an important role in gametocyte development. Interestingly, the insertion of a transposon into the coding sequence of the P. falciparum ortholog gene (PF3D7_1317200) resulted in the absence of gametocytes, suggesting that it might play a role in gametocytogenesis; however, the role of the ortholog of this gene in gametocytogenesis could not be conclusively determined because the parasite line containing a transposon insertion in the PF3D7_1317200 gene also had a missense mutation in the Pfap2-g gene (24,25). Our data clearly showed that disruption of Pyap2-g3 significantly reduced the number of gametocytes, leading to the absence of sporozoites even though a small number of day 8 oocysts were observed (Fig.…”
Section: Figmentioning
confidence: 99%
“…The factor that might stimulate the differenciation to gametocytes might varies such as the host immune responses, oxidative stress or other condition that make the parasite in uncomfortable condition. 18 The presence of gametocyte in the blood circulation of malaria patient must be take as highly priority of attention since it is critical for transmission to other people. Anti gametocytocidal drug must be given and prevention to mosquito bite are also very essential.…”
Section: Discussionmentioning
confidence: 99%
“…bone marrow) during development and only mature stage V gametocytes circulating in the blood stream where they can be transmitted to mosquitoes [8]. After the stochastic, epigenetically driven [9][10][11][12] gametocyte conversion rate of ~1% of the asexual population [6], the immature stage I-III gametocytes are to some extent biochemically more aligned to asexual parasites than their stage V partners [8] whose metabolism effectively decreases to only retain household activities such as ATP production and redox maintenance [13]. This raises unique issues in the identification of drugs active on P. falciparum gametocytes, and specifically on the mature stage V forms, compared for instance to those of P.…”
Section: Malaria: From Control To Eliminationmentioning
confidence: 99%